USTEKINUMAB IN CROHN’S DISEASE MANAGEMENT: A BRAZILIAN OBSERVATIONAL STUDY - Paula Cenira Senger de CASTRO; Daniéla Oliveira MAGRO; Rodrigo Bremer NONES; Thaisa Kowalski FURLAN; Eron Fábio MIRANDA; Paulo Gustavo KOTZE (Arquivos de Gastroenterologia, 2022)
ABSTRACT Background: Real-world data on the use of Ustekinumab (UST) in Brazilian and Latin American patients with Crohn’s disease (CD) are scarce. Objective: The primary endpoint was assessment of clinical remission at weeks 8 and 52, and secondary endpoints were: assessment of clinical response at weeks 8 and 52, endoscopic remission, adverse events, and rates of CD-related abdominal surgery during follow-up. Methods: observational and retrospective study, including patients with CD treated at two centers, who received UST at any time during their treatment. Remission and clinical response were defined as a Harvey-Bradshaw index ≤4 and ≥3 points reduction, respectively. Results: Seventy-four patients were included, 85.1% previously exposed to anti-TNFs. Clinical remission was observed in 45.8% and 59.4% of patients at weeks 8 and 52, respectively. The clinical response rates were 54.2% and 67.6% at weeks 8 and 52. Endoscopic remission was observed in 21.8% of patients. Seventeen patients had adverse events, mostly mild infections, with 22.9% of patients undergoing abdominal surgery (ileocolectomy being the most common procedure). Conclusion UST therapy resulted in significant rates of remission and clinical response, as described in other real-world studies. Few patients had adverse events during treatment, showing its adequate safety profile.